Differentiating non-lactating mastitis and malignant breast tumors by deep-learning based AI automatic classification system: A preliminary study - Zhou, Ying; Feng, Bo-Jian; Yue, Wen-Wen; Liu, Yuan; Xu, Zhi-Feng; Xing, Wei; Xu, Zhao; Yao, Jin-Cao; Wang, Shu-Rong; Xu, Dong (Frontiers in Oncology, 2022)
Objective To explore the application values of deep-learning based AI automatic classification system, on the differential diagnosis of non-lactating mastitis and malignant breast tumors Methods A total of 707 patients suffering from breast lesions were selected from the following 3 medical centers, including Zhejiang Cancer Hospital, Hebei Province Hospital of Traditional Chinese Medicine, and Yantai Affiliated Hospital of Binzhou Medical University, and the time period was set from april 2020 to september 2021. All selected cases firstly accepted the routine breast ultrasound diagnosis, followed by the interpretations from a senior sonographer with more than 15 years of work experiences, and an intermediate-aged sonographer with more than 5 years of work experiences, independently. Meanwhile, a third physician also interpreted the same ultrasound images by deep-learning based AI automatic classification system, independent of the interpretation results from the previous two physicians. The Kappa test was performed to evaluate the consistency between the conventional ultrasound interpretation results and pathological results interpreted from physicians with different working experiences. Results The accuracy, sensitivity and specificity for intermediate-aged sonographers and senior sonographers, were 76.92%(590/767), 84.71%(216/255), 73.95%(374/512), and 87.35%(670/767), 86.27%(220/255), 87.89%(450/512), respectively (P＜0.001). In contrast, if the threshold was set as 0.5, the accuracy, sensitivity and specificity from deep-learning based AI automatic classification system, were 83.00%, 87.20% and 85.33%, separately, and the area under the curve(AUC) was 92.6. The results of the Kappa consistency test indicated that, the diagnosis results from the image interpretations by senior physicians, and deep-learning based AI automatic classification system, showed high consistency with postoperative pathological diagnosis results, and the Kappa values are 0.72 and 0.71, respectively, with the P value of less than 0.001. In contrast, the consistency between the image interpretation results from intermediate-aged physicians with less working experiences, and postoperative pathological diagnosis results, seemed to be relatively lower, with Kappa value of only 0.53 and P value of less than 0.001. Conclusions 　The deep-learning based AI automatic classification system, is expected to become a reliable auxiliary way to distinguish the non-lactating mastitis and malignant breast tumors, due to its high sensitivity, accuracy and specificity.